2015
DOI: 10.1080/01446193.2015.1050425
|View full text |Cite
|
Sign up to set email alerts
|

The fourth pillar of infrastructure sustainability: tailoring civil infrastructure to social context

Abstract: This research proposes technical performance over time as a fourth pillar of sustainability theory for infrastructure. It also describes a method that allows us to discover how changes in the technical pillar (operationalised as reduced breakage rates) may moderate the influence of the social pillar (operationalised as repair rates) on sanitation infrastructure outcomes. Oral histories were used to develop a history of sanitation for each of 152 poor households in four rural communities in Bangladesh that have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Additionally, durable structures and systems are often perceived as the most sustainable and resilient (e.g. Kaminsky, 2015;Mirza, 2006). This is not to say that components of decentralized systems should not be durable; the planned obsolescence competency arises from the organizational structure of the infrastructure, not from the durability of the components.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, durable structures and systems are often perceived as the most sustainable and resilient (e.g. Kaminsky, 2015;Mirza, 2006). This is not to say that components of decentralized systems should not be durable; the planned obsolescence competency arises from the organizational structure of the infrastructure, not from the durability of the components.…”
Section: Discussionmentioning
confidence: 99%
“…From the worldwide picture, beyond the individual building scale, a variety of another sustainability assessment rating schemes (i.e., Envision, CEEQUAL, IS Rating Tool, BCA Green Mark) have been developed and implemented to assess the sustainability of the infrastructure projects in terms of their development and operation [26]. Unanimously scholars agreed that among the triple bottom line of sustainable principle underlying those developed rating schemes, environmental aspect is the most important one for attaining overall sustainability [28,33]. However, literature shows that there are arguments about the most effective and efficient IOP Publishing doi:10.1088/1755-1315/1238/1/012010 6 infrastructure rating system (used for managing the sustainability practices) among the specialists and researchers [18].…”
Section: The Adoption and Adaption Of Ceequal Methodsmentioning
confidence: 99%
“…We defined the outcome of PASS 'success' as 'in use and technically functional at point in time 12 months after installation' based on several WASH QCA studies that indicated that function and use were both important in the determination of whether WASH interventions were fulfilling their intended goals (Kaminsky & Javernick-Will 2012;Kaminsky 2015;Marks et al 2018;Davis et al 2019b). The use of PASS in conjunction with other WASH infrastructure in the home (e.g.…”
Section: Social Conditionsmentioning
confidence: 99%
“…Understanding the inputs and factors that lead to successful household WASH systems can help implementers more efficiently manage projects and improve the outcomes within unserved communities. The installation of PASS units required typical institutional inputs for infrastructure projects, such as capital funding and institutional support (Ashley et al 2008;Kunz et al 2015;Adank et al 2018), and typical technical process steps, such as the creation of engineering plans, and construction according to those plans with appropriate materials (Mihelcic et al 2009;Kaminsky 2015). Additionally, because PASS is a novel mid-tech novel system, social factors like homeowner engagement, enthusiasm for mid-tech, operation and maintenance (O&M) training, ownership, and end-user satisfaction were also hypothesized to impact the success of the systems.…”
Section: Introductionmentioning
confidence: 99%